A comparison of tensile weld strength and microstructural changes in four arch wires, before and after immersion in 1.23% acidulated phosphate fluoride solution: An in-vitro study - Shantanu Tela; Veera Bhosale; Ravindranath Sable; Roopa Abdullah; Rajshekhar Halli (Wolters Kluwer Medknow Publications, 2013)
Objectives: The objective of this study is to evaluate and to compare the tensile weld strengths and microstructural changes in four archwires namely beta titanium, stainless steel (SS), blue elgiloy and timolium before and after immersion in 1.23% acidulated phosphate fluoride (APF) solution. Materials and Methods: The mean tensile weld strength of a weld joint of four arch wires were compared pre-fluoride (Group 1) with post fluoride (Group 2) and the microstructural characteristics of weld joints were evaluated under an optical microscope. Results: The mean tensile weld strength for beta titanium was 445.64 N/mm 2 , blue elgiloy was 363.26 N/mm 2 , SS was 358.30 N/mm 2 and timolium was 308.62 N/mm 2 . After immersion in fluoride the mean tensile strength for beta titanium was 427.16 N/mm 2 , blue elgiloy was 359.86 N/mm 2 , SS is 349.44 N/mm 2 and timolium is 294.86 N/mm 2 . After immersion in fluoride, the beta titanium and SS had a smooth fusion at the center of weld assembly with characteristic nugget formation. The beta titanium weld assembly had greater tensile weld strength than other welded assemblies. Blue elgiloy ranked second, whereas SS and timolium were third and fourth respectively. Conclusion: The wires in descending order of their mean tensile weld strength, on evaluation of their weld joints were found to be: Beta titanium > blue elgiloy > SS > timolium. The reduction in tensile weld strength was statistically insignificant for all the archwires after exposure to 1.23% APF at 37°C for 90 min.